2020
DOI: 10.1007/s10800-019-01385-0
|View full text |Cite
|
Sign up to set email alerts
|

Electrodeposition of titanium–vanadium alloys from chloride-based molten salts: influence of electrolyte chemistry and deposition potential on composition, morphology and microstructure

Abstract: In the present study, we demonstrate co-deposition of titanium and vanadium from a eutectic LiCl-KCl electrolyte enriched with VCl 3 and TiCl 2 at 700 K. While the addition of metallic titanium to the electrolyte caused vanadium depletion by a displacement reaction, metallic vanadium addition created and stabilized divalent vanadium ions in the melt, which are supposed to positively affect the deposition process. Various electrochemical experiments were carried out with different electrolyte concentrations, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 43 publications
0
4
0
Order By: Relevance
“…It is expected to be filled with randomly oriented, poorly grown crystals. 44 Contrarily, R4-PPED exhibits plain hexagonal plate structures that are stacked (Fig. 7b).…”
Section: Resultsmentioning
confidence: 97%
“…It is expected to be filled with randomly oriented, poorly grown crystals. 44 Contrarily, R4-PPED exhibits plain hexagonal plate structures that are stacked (Fig. 7b).…”
Section: Resultsmentioning
confidence: 97%
“…Guo et al (2015) achieved the deposition of Ni over glassy carbon at -1.25 V. For Ti, the electrodeposition occurs in a similar route at very negative potentials using complex agents and basic electrolytes (Rao and Triveti 2005). Gussone et al (2020) carried out the electrodeposition of Ti in molten salt medium at -0.4 V and 700 ºK indicating that the eletrodeposition of Ti is extremely endothermic and, at room temperature, the electrodeposition is impossible and competitive with the hydrogen evolution. (pentavanadyl cation) in aqueous medium at low pH values (< 3.6) at 10 mM concentration but, when the concentration increases to 1 mM, the pH decreases to 1.3 promoting the formation of V 2 O 5 between pH 1.3 and 3.6.…”
Section: Resultsmentioning
confidence: 99%
“…Considering the production of titanium powder from titanium sponge as the raw material, the shuttle reactions due to disproportionation (the backward reaction of Ti 2+ to Ti 3+ and Ti metal) were studied at 1023 K in molten NaCl KCl by Lu et al 103) and in molten MgCl 2 LiCl by Wu et al 104) Their results showed that Ti 2+ is more stable in these molten salts than in fluoride melts. A Ti-rich TiV alloy with a cauliflower-like morphology was deposited from LiClKCl at 700 K. 105) Fig. 5 Mechanism of Mg reduction in MgCl 2 melt proposed by Fang et al 87,88) A d v a n c e V i e w Kumamoto et al 106) chose the eutectic LiClKClCsCl system to conduct the electroreduction of Ti 2+ to Ti at low temperatures such as 573 K. The addition of F ¹ increases the current density of electrodeposition because of the increase in the total concentration of soluble Ti ions in the molten salt.…”
Section: Low-temperature Processesmentioning
confidence: 99%